ANALYSIS OF CS-137 RADIONUCLIDE ON THE EAST JAKARTA FLOOD CANAL WATER SAMPLES USING GAMMA SPECTROMETER - Indah Dwi Cahyati; Hendrawati Hendrawati; Ghulam Fathul Amri (Jurnal Sains dan Teknologi Nuklir Indonesia (Indonesian Journal of Nuclear Science and Technology), 2021)
Radionuclide Cs-137 is a radioactive element that is soluble in water, so its distribution in the environment is influenced by mixing and diffusion, so that Cs-137 radionuclide can cause harmful effects on biotic and abiotic components in the waters. The East Jakarta Flood Canal is a macro drainage system for the city of DKI Jakarta that drains water to Marunda beach, most of the water quality has been polluted with light to heavy levels of pollution. This study aims to determine the water quality of the East Jakarta Flood Canal including in situ and ex situ physical and chemical properties parameters (temperature, pH, salinity and TDS) and Cs-137 radionuclide concentration parameters and the distribution pattern of Cs-137 radionuclides at each sampling point. The samples used were water and kale, the samples were filtered and concentrated from the initial volume of 20 liter of water to 1 liter of water and 10 kilograms to 1 kilogram of Kale plant. The levels of Cs-137 were measured with a gamma spectrometer instrument for 3600 seconds, then data analysis was carried out. The results obtained are the concentration level of Cs-137 in Simplo KBT water ranging from 0-1.571 Bq/L, for duplo 0-0.424 Bq/L while for kale plant 0-3,228 Bq/Kg the overall results are within the quality standard limits set by regulations. the head of BAPETEN Number 7 of 2013 concerning the limit value of environmental radioactivity, which is 2.6Ã—102 Bq/L.